An Empirical Investigation into Child Abuse and Neglect in India Burden, Impact and Protective Measures - Deb, Sibnath (SpringerBriefs in Well-Being and Quality of Life Research,, 2018)
This book provides a comprehensive overview of child abuse and neglect globally in general terms and with empirical evidence from Puducherry, India. The study unearths the reality concerning child safety and raises a number of questions about child safety measures at the institutional and family levels. It recommends evidence-based and culture-specific preventive measures for child protection. The empirical evidence presented here provides important and useful information to school administrators on the issues of child abuse and neglect, for them to take evidence-based protective measures both at school and at home. For cross-cultural comparison, the findings are of interest to international scholars and academics. This work is useful for policy makers, educators, NGO personnel, child rights activists and opinion leaders in government departments dealing with children, and for researchers in the fields of psychology, social work, nursing, pediatric, forensic medicine, and public health. .